WCDMA Network Planning and Optimisation - Yeo, K.; Tiong, Teck Chai (IEEE, 2008)
Radio network planning and optimization for third generation (3G) wideband code division multiple access (WCDMA) in frequency division duplex (FDD) mode requires more advanced techniques compared to second generation (2G) network to achieve optimum network coverage and system capacity. The planning process covered configuration planning, topology planning and Quality of Services (QoS). In configuration planning, the radio network planner selects the optimum configuration of the base station (BS) for the planned cell to meet the network quality targets taking into consideration investment and operating cost limits. Topology planning covers combined coverage and capacity planning including base station site and antenna configuration. QoS ensures that mobile subscribers receive quality circuit switched (CS) and packet switched (PS) services. The study is carried out at the Senadin base station located in Miri, Sarawak with permission by CELCOM.